2014
DOI: 10.3906/sag-1301-67
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic importance of chromosomal abnormalities, Y chromosome microdeletions, and CFTR gene mutations in individuals with azoospermia or severe oligospermia

Abstract: IntroductionNative Turkish ducks are raised primarily for meat, eggs, and feathers. Native duck genotypes have been extensively raised for many years on family farms in some regions of the country. However, since we have no statistical data on duck breeding potentials in Turkey, it is only known that there are very few small-scale duck farms raising ducks (1,2). Ducks are easily raised and they are hardy and less susceptible to many of the common poultry diseases such as leucosis, Marek's disease, infectious b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Sex chromosomes abnormalities were predominating, with frequency of 9.09%. This was similar to the results of the studies done in other populations where numerical and structural autosomal chromosome aberrations were also less common (FORESTA et al, 2002;YATSENKO et al, 2010;OCAK et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Sex chromosomes abnormalities were predominating, with frequency of 9.09%. This was similar to the results of the studies done in other populations where numerical and structural autosomal chromosome aberrations were also less common (FORESTA et al, 2002;YATSENKO et al, 2010;OCAK et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In general, frequency of AZF microdeletions is 10%, going up to 15% in patients with oligospermia and up to 20% in azoospermic men (FORESTA et al, 2002). According to the literature, the ranges of Y-chromosome microdeletions in infertile men vary very widely from 1-55% (OCAK et al, 2014). The differences in reported frequencies may reflect variations in the sample group, ethnic and geographic differences and selection of STS markers (NG et al, 2009;KRAUSZ et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mafra et al (2011) reported chromosomal abnormalities for 6.2% of infertile Brazilian men with severe oligozoospermia or non-obstructive azoospermia and the total prevalence of chromosomal abnormalities was found to be 11.2% in infertile males with oligozoospermia and azoospermia in southeast Turkey (Balkan et al, 2008). Ocak et al (2014) reported structural or numerical chromosomal abnormalities to be present in 12% of patients with azoospermia or severe oligospermia and 10.9% of Chinese patients with azoospermia or severe oligozoospermia were found to have chromosomal abnormalities (Zhou-Cun et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with AZFa and b microdeletions, spermatozoa could be found in no single case according to the literature (Simoni et al, 2008;Navarro-Costa et al, 2010), while in the case of AZFc microdeletion, a SR rate of more than 50% can be expected according to the literature (Simoni et al, 2008;Navarro-Costa et al, 2010;Krausz et al, 2014). Some authors believe that the incidence of Y chromosome microdeletions in Germany with 2-3% of men with NOA may be lower than in other countries (Simoni et al, 2008), while the prevalence in infertile men was published for Turkey with 6% and China with up to 13% (Ocak et al, 2014;Elfateh, 2014).…”
Section: Discussionmentioning
confidence: 99%